2021
DOI: 10.31449/inf.v45i5.3560
|View full text |Cite
|
Sign up to set email alerts
|

Attribute Reduction Algorithm Based Early Warning Model of Sports Injury

Abstract: With the continuous development of track and field sports, a relatively complete and scientific system has been formed in terms of training, and more attention has been paid to the planned training of teenagers for many years, psychological training and recovery training, and strengthening medical supervision and scientific research. In order to speed up the scientific training of track and field and improve the level of track and field training in China, in view of the characteristics of track and field injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The results of the study showed that there was a significant correlation between the adequacy of athletes' preparation activities and the rationality of training programs and athletes' injuries. Wang and his research partner developed a mutual information sports injury warning model based on an attribute parsimony algorithm, which was designed for youth athletics [7]. Simulation experiments found that the model was able to warn youth track and field athletes of injuries with 80% correctness, but the model suffered from a local optimal solution.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the study showed that there was a significant correlation between the adequacy of athletes' preparation activities and the rationality of training programs and athletes' injuries. Wang and his research partner developed a mutual information sports injury warning model based on an attribute parsimony algorithm, which was designed for youth athletics [7]. Simulation experiments found that the model was able to warn youth track and field athletes of injuries with 80% correctness, but the model suffered from a local optimal solution.…”
Section: Related Workmentioning
confidence: 99%
“…When nN  , the control parameters must be such that the inertia weights can reach or converge to (min)  , and the inertia weights at this time are shown in Eq. (7).…”
mentioning
confidence: 99%
“…These datasets undergo preprocessing to clean and transform the data into a format suitable for analysis [10].Next, data mining techniques such as machine learning algorithms are applied to uncover hidden patterns and relationships within the data. Classification algorithms can be utilized to categorize athletes into different risk groups based on their likelihood of injury [11]. Clustering techniques can identify subgroups of athletes with similar risk profiles, allowing for targeted prevention strategies.…”
Section: Introductionmentioning
confidence: 99%